Aerodynamic study of spinning effects of velocity variation 40 km/h on sports ball - Singh, A.; Shakya, A. K.; Birla, S. (International Research Journal of Modernization in Engineering Technology and Science, 2021)
In this competitive era of sports, ball based game gaining popularity and everybody want to win so the knowledge of sports engineering become very important. We either do not know about science behind it or very less information is available in open domain. Even a very little information can play crucial role to win the game. In every game like volleyball, football, golf, cricket, rugby, baseball, tennis aerodynamics play an important role. Most of the ball are spherical in shape so the aerodynamics study of smooth sphere has been done as Reynolds No. increases Drag coefficient decreases and in transient region drag reduces abruptly. To study the spin effect on tennis ball, modelled tennis ball of diameter 69mm and seam width 5mm and surface roughness 5mm have used, velocity variation 40- 120km/h of increment 40km/h and spin rate vary from 500rpm to 3000rpm increment of 500rpm. As spin rate increases both drag and lift coefficient increases at same velocity but drag and lift coefficient decreases as velocity of ball increases at same spin rate. Variation in side drag coefficient have been studied and found that there are no significant effect of side force on the ball because of seam.